2023
DOI: 10.3390/agriculture13010173
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Dietary Amino Acid Ratio Based on Egg Quality for Japanese Quail Breeder

Abstract: The objective of this study was to determine the ideal amino acid ratio for Japanese quail based on egg quality. In total, 120 Japanese quail were used. A completely randomized design was used with 12 treatments and 10 replicates per treatment. The treatments consisted of a balanced protein (BP) and the subsequent 11 diets were obtained by the 40% deletion of the BP a specific test for Lys, Met + Cys, Thr, Trp, Arg, Gly + Ser, Val, Ile, Leu, His, and Phr + Tyr. The trial lasted for 25 days. At the end of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The dietary threonine concentration reported for laying quails are estimated higher than those determined in this study for Japanese quail breeders. In agreement with our result in the current study, dThr requirement for Japanese quail breeders was estimated at 0.59% (Carvalho et al, 2022, 2023), which was 14% and 5% lower than reported by Ramalho de Lima et al (2013) and Sarcinelli et al (2020), respectively. Carvalho et al (2022) concluded that Japanese quail breeders have lower dietary efficiency than commercial birds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The dietary threonine concentration reported for laying quails are estimated higher than those determined in this study for Japanese quail breeders. In agreement with our result in the current study, dThr requirement for Japanese quail breeders was estimated at 0.59% (Carvalho et al, 2022, 2023), which was 14% and 5% lower than reported by Ramalho de Lima et al (2013) and Sarcinelli et al (2020), respectively. Carvalho et al (2022) concluded that Japanese quail breeders have lower dietary efficiency than commercial birds.…”
Section: Discussionsupporting
confidence: 93%
“…Breeder birds need amino acids for maintenance, tissue growth and fertile EP (Carvalho et al, 2022). Therefore, maternal nutrition can modify the composition and characteristics of eggs and consequently affect embryonic development (Carvalho et al, 2023; Li et al, 2019). Among indispensable amino acids, threonine is often the third limiting amino acid for poultry fed corn‐soybean meal diets (Hossaninejad et al, 2021; Jiang et al, 2019) and plays a vital role in the gastrointestinal tract, immunity, protein synthesis, FE and reproductive system (Mehri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second article by Carvalho L.C. et al [17] highlights a very interesting topic, and the authors provide a substantial contribution to the determination of the optimal amino acid ratio for Japanese quail based on the quality of egg production. A completely randomized design was used, with 120 Japanese quails, 12 treatments and 10 replicates per treatment.…”
mentioning
confidence: 99%